Sleep-awake energy efficient distributed clustering algorithm for wireless sensor networks. (November 2016) - Ahmed, Gulnaz; Zou, Jianhua; Fareed, Mian Muhammad Sadiq; Zeeshan, Muhammad
Highlights: A new energy efficient routing algorithm has been proposed for cluster based wireless sensor networks. SEED achieves O(1) message exchange complexity per sensor node and time complexity for cluster formation is O(N) for WSN having N sensor nodes. We introduce sub-clustering in SEED to decrease the redundant data transmissions towards the base station. The proposed model utilizes sleep-awake awareness to save the available power. Graphical abstract: Abstract: Hierarchical clustering technique is an effectual topology control methodology in Wireless Sensor Networks (WSNs). This technique is used to increase the life time of the network by reducing the number of transmissions towards the base station. We propose and validate a new routing protocol termed as Sleep-awake Energy Efficient Distributed (SEED) clustering algorithm. We divide the network sensing field into three energy regions because in SEED cluster heads are communicating directly with the base station. The cluster heads of the high energy region are communicating with the base station through a longer distance and paying extra energy cost as compared to the cluster heads of the low energy region. Same application base sensor nodes form sub-clusters to decrease the number of transmissions towards the base station. In every round, one node from these sub-clusters nodes awake and transmit the data and the rest of them sleep to save available resources. We select six criteria to check the performance of our algorithm. The simulation results show that SEED achieves longer network life time and high throughput as compared to the existing clustering protocols.